The typology of memoirs and autobiographical editions: dynamic aspects - M. A. Lappo (Библиосфера)
The article considers types of memoirs and autobiographical books actual for the contemporary practice. It refines typological characteristics associated with new information technologies and, as a consequence, communication methods. A group of such products is formed not only with traditional book editions, but also online texts, because they are independent publications and/or more often become a source of traditional books. At the heart of the working typology of memoirs and autobiographical books are the text genre features accounting the following categories: «updating the past», «an autodescription», «an edition material design» (printed or electronic), and others.